Safety, tolerability and efficacy of lixisenatide as monotherapy in Japanese patients with type 2 diabetes mellitus: An open‐label, multicenter study - Seino, Yutaka (J Diabetes Investig, 2017)
AIM/INTRODUCTION: To assess the overall safety of lixisenatide monotherapy in Japanese patients with type 2 diabetes mellitus. MATERIALS AND METHODS: Patients with type 2 diabetes mellitus, previously treated with ≤1 oral antidiabetic drug, were enrolled in an uncontrolled, open‐label, single‐arm study over 24 and 52 weeks. Any oral antidiabetic drug treatment was stopped at the start of the 6‐week run‐in period. From baseline, patients received once‐daily lixisenatide monotherapy (10 μg for 1 week, 15 μg for 1 week, 20 μg thereafter) for 52 weeks (first 140 patients enrolled) or 24 weeks (subsequently enrolled patients). The primary end‐point was safety over 24 and 52 weeks. Secondary efficacy end‐points included absolute change in glycated hemoglobin, fasting plasma glucose and bodyweight from baseline. RESULTS: Of 428 patients screened, 361 and 140 were treated for 24 and 52 weeks, respectively; 88.4 and 90.0% completed treatment. During the 24‐ and 52‐week treatment periods, 268/361 (74.2%) and 117/140 (83.6%) patients, respectively, had treatment‐emergent adverse events; the most frequently reported was nausea (33.2 and 31.4%, respectively). The risk of severe hypoglycemia was low; only one case was reported. Lixisenatide treatment resulted in a decrease in mean glycated hemoglobin A1c (−0.98 and −0.86%), fasting plasma glucose (−1.05 and −0.85 mmol/L), and bodyweight (−1.33 and −1.48 kg) for the 24‐ and 52‐week treatment periods, respectively. CONCLUSIONS: Once‐daily lixisenatide monotherapy was associated with a safety profile in line with the glucagon‐like peptide‐1 receptor agonist class, and improved glycemic control in Japanese patients with type 2 diabetes mellitus.